A geometric assessment method for estimating dimensional change of retrieved dual mobility liners for total hip arthroplasty. (June 2023) - Smeeton, Mackenzie; Isaac, Graham; Wilcox, Ruth; Anderson, James; Board, Tim; Van Citters, Douglas W; Williams, Sophie
Despite their emerging use, the current understanding of the in-vivo functional mechanisms of Dual Mobility (DM) Total Hip Replacements (THRs) is poor, and current characterisation methodologies are not suitable for the unique function and design of these types of devices. Therefore, the aim of this study was to develop a geometric characterisation methodology to estimate dimensional change across the articulating surfaces of retrieved DM polyethylene liners so that their invivo function may be better understood. The method involves the acquisition of three-dimensional coordinate data from the internal and external surfaces of DM liners. The data is processed using a bespoke MATLAB script which approximates the unworn reference geometry of each surface, calculates geometric variance at each point and produces surface deviation heatmaps so that areas of wear and/or deformation may be visualised across the implant. One as-manufactured and five retrieved DM liners were assessed, which demonstrated the efficacy, repeatability and sensitivity of the developed method. This study describes an automated and non-destructive approach for assessing retrieved DM liners of any size and from any manufacturer, which may be used in future research to improve our understanding of their in-vivo function and failure mechanisms.